Homage to Evangelista Torricelli’s Opera Geometrica 1644–2024 - Pisano, Raffaele. author. aut Link
XVI, 1113 p. 553 illus., 507 illus. in color.
Keywords: Evangelista Torricelli exemplifies the use the moderns made of the ancients' mathematical methods. Celebrating Evangelista Torricelli's monumental Opera geometrica, this book marks 380 years since its publication (1644-2024). This homage to Torricelli introduces the magnificent major work in Mechanics and Mathematics of a brilliant Archimedean–and–Galilean scientist to modern readers. Opera geometrica deals with Motion & Mechanics and Geometry & Infinitesimals. In quibus Archimedis doctrina Torricelli also presents his mechanical principle of equilibrium – the foundation of the modern Principle of Virtual Work/Static. This outstanding source and research book spotlights the relevance and originality of Torricelli’s Mechanics, and is the first and most profound analysis of the Opera geometrica to date. The historical study is achieved in extensive Introduction, 5 Essays and an accurate Transcription of Opera geometrica with parallel side–by–side text, including substantive explicative notes. The book is an accessible avenue to understanding this work by leading authorities who offer much-needed insights into the relationship Physics–Mathematics, Mechanics and Fundamentals. It appeals to historians, epistemologists and scientists.